1993
DOI: 10.1152/ajprenal.1993.265.5.f736
|View full text |Cite
|
Sign up to set email alerts
|

NHE3: a Na+/H+ exchanger isoform of renal brush border

Abstract: Na+/H+ exchangers in the brush-border (luminal, apical) membrane of renal proximal tubules are responsible for active, transcellular reabsorption of NaHCO3 and NaCl. Although well characterized kinetically, the protein that mediates Na+/H+ exchange in the renal brush border has not been identified. Several Na+/H+ exchanger genes, including NHE1, NHE2, NHE3, and NHE4, are expressed in the kidney. To identify the NHE3 gene product and to determine its cellular and subcellular localization in the rabbit kidney, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
218
1
8

Year Published

1996
1996
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(239 citation statements)
references
References 46 publications
12
218
1
8
Order By: Relevance
“…NHE1 contains both N-and O-glycosylated residues, and mutation of Asn-75 abolishes the N-linked glycosylation (13). In contrast, rabbit NHE2 exhibits only O-linked glycosylation (14) and NHE3 appears not to be glycosylated (13,15) (Fig. 1).…”
Section: Structural Featuresmentioning
confidence: 99%
See 1 more Smart Citation
“…NHE1 contains both N-and O-glycosylated residues, and mutation of Asn-75 abolishes the N-linked glycosylation (13). In contrast, rabbit NHE2 exhibits only O-linked glycosylation (14) and NHE3 appears not to be glycosylated (13,15) (Fig. 1).…”
Section: Structural Featuresmentioning
confidence: 99%
“…Its precise physiological roles are unclear, but when transfected into mutagenized cells devoid of endogenous NHE activity, NHE2 is capable of regulating pH i , cellular volume, and proliferation in a manner resembling NHE1 (21). Immunological studies have localized NHE3 to the apical membranes of renal proximal tubule (15) and intestinal (20,22) epithelia, implicating this isoform in Na ϩ absorption. The accompanying luminal secretion of H ϩ is essential for HCO 3 Ϫ reabsorption in renal tubules.…”
Section: Tissue and Subcellular Distributionmentioning
confidence: 99%
“…Several lines of evidence strongly support the conclusion that NHE3 is the principal NHE isoform responsible for apical membrane Na + /H + exchange in the proximal tubule. First, studies using isoform-specific antibodies have demonstrated that NHE3 is expressed on the brush border membrane of proximal tubule cells (Biemesderfer et al, 1993b;Biemesderfer et al, 1997). Second, the pattern of sensitivity to different inhibitors of Na + /H + exchange in renal brush border vesicles and of bicarbonate absorption in microperfused proximal tubules is most consistent with the properties of NHE3 among the known NHE isoforms (Vallon et al, 2000).…”
Section: Introductionmentioning
confidence: 86%
“…Thus far, five sodium proton exchangers (NHE1, NHE2, NHE3, NHE4 and NHE8) have been identified in plasma membrane of renal tubular cells (Biemesderfer et al, 1992;Biemesderfer et al, 1993a;Amemiya et al, 1995;Chambrey et al, 1997;Chambrey et al, 1998). Of these, NHE3, the most abundant NHE isoform in renal tissue, is confined to the apical membrane of proximal tubule and thin and thick ascending limb.…”
Section: Introductionmentioning
confidence: 99%
“…Other isoforms, in contrast, have a more restricted tissue distribution and are believed to mediate specialized functions. These include NHE3, which is the predominant isoform found on the apical membranes of epithelial cells in the kidney and gastrointestinal tract (4,5). In these tissues, NHE3 catalyzes the entry of luminal Na ϩ into the cells, which in turn drives the transport of salt and osmotically obliged water across the epithelium.…”
Section: Members Of the Namentioning
confidence: 99%